A single-institution phase I feasibility study of dose-escalated IMRT for non-operative locally advanced esophageal carcinoma. (September 2021) - Vlacich, Gregory; Ballard, Andrew; Badiyan, Shahed N.; Spraker, Matthew; Henke, Lauren; Kim, Hyun; Lockhart, A. Craig; Park, Haeseong; Suresh, Rama; Huang, Yi; Robinson, Cliff G.; Bradley, Jeffrey D.; et al.
Highlights: Dose escalation with IMRT to 60 Gy for esophageal cancer is feasible. Dose escalation with cisplatin/5-FU still results in significant toxicity. Improved local control, but comparable survival compared to historical controls. Pretreatment weight loss was found to be an independent predictor of poor survival. Our dose escalation study is one of few with predominant adenocarcinoma histology. Abstract: Background and purpose: Radiation dose escalation to improve poor outcomes with chemoradiation in locally advanced esophageal carcinoma is limited in part by increased toxicity. This Phase I study investigates the use of IMRT to improve tolerability of dose escalation. Materials and methods: A single-institution, prospective study was conducted between 2007 and 2013 for individuals with inoperable esophageal carcinoma. Gross disease received 60 Gy in 30 fractions and at-risk sites received 54 Gy with simultaneous integrated boost. Concurrent chemotherapy primarily consisted of cisplatin/5-FU. The primary objective was to assess feasibility (<15% rate of grade 4–5 toxicity). Secondary objectives included assessment of overall survival (OS), progression free survival (PFS), and locoregional (LRR) and distant recurrence. Results: Twenty-six patients were enrolled with median follow up of 17.6 months (range 0.1 to 152.0). The majority were AJCC 7th edition Stage III (54%), distal esophagus primary (81%), and adenocarcinoma histology (85%). Twenty-one patients (81%) completed their course of radiation therapy, while only 55% received 2 cycles of concurrent cisplatin/5-FU. One grade 5 and one grade 4 cardiac event occurred, both during chemoradiation and before receiving 50 Gy. The 3-year OS was 48.6% (95% CI: 32.5 to 72.2%) and PFS was 28.5% (95% CI: 14.6 to 55.5%). Half developed distant failure with LRR occurring in 10 patients (38%), isolated in 5 patients. Conclusion: While feasibility was demonstrated, toxicity and compliance remained limiting factors with outcomes similar to historical controls. There remains an uncertain role for dose escalation in definitive management of locally advanced esophageal cancer.